The Mobilome; A Major Contributor to Escherichia coli stx2-Positive O26:H11 Strains Intra-Serotype Diversity - Delannoy, Sabine; Mariani-Kurkdjian, Patricia; Webb, Hattie E.; Bonacorsi, Stephane; Fach, Patrick (Frontiers in Microbiology, 2017)
Shiga toxin-producing Escherichia coli of serotype O26:H11/H- constitute a diverse group of strains and several clones with distinct genetic characteristics have been identified and characterized. Whole genome sequencing was performed using Illumina and PacBio technologies on eight stx2-positive O26:H11 strains circulating in France. Comparative analyses of the whole genome of the stx2-positive O26:H11 strains indicate that several clones of EHEC O26:H11 are co-circulating in France. Phylogenetic analysis of the French strains together with stx2-positive and stx-negative E. coli O26:H11 genomes obtained from Genbank indicates the existence of four clonal complexes (SNP-CCs) separated in two distinct lineages, one of which comprises the “new French clone” (SNP-CC1) that appears genetically closely related to stx-negative attaching and effacing E. coli (AEEC) strains. Interestingly, the whole genome SNP (wgSNP) phylogeny is summarized in the cas gene phylogeny, and a simple qPCR assay targeting the CRISPR array specific to SNP-CC1 (SP_O26-E) can distinguish between the two main lineages. The PacBio sequencing allowed a detailed analysis of the mobile genetic elements (MGEs) of the strains. Numerous MGEs were identified in each strain, including a large number of prophages and up to four large plasmids, representing overall 8.7 to 19.8% of the total genome size. Analysis of the prophage pool of the strains shows a considerable diversity with a complex history of recombination. Each clonal complex (SNP-CC) is characterized by a unique set of plasmids and phages, including stx-prophages, suggesting evolution through separate acquisition events. Overall, the MGEs appear to play a major role in O26:H11 intra-serotype clonal diversification.